Schickendantziella trichosepala (Alliaceae), nueva cita para Bolivia - Negritto, María A.; Ruiz, Eduardo; Beck, Stephan; Escobar, Inelia; Baeza, Carlos M. (Gayana Botánica, 2010)
Schickendantziella trichosepala (Speg.) Speg., a new record from Bolivian flora. The taxonomic history, description, iconography and geographical distribution of this monotypic South American genus are presented.